"Institute of Music University of Zielona Góra Presents Big Band Series" - Szymaniuk, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is dedicated to new releases under the general title "Institute of Music University of Zielona Góra Presents Big Band Series", in the field of repertoire dedicated to big band jazz orchestras. The author presents a series of eight big band charts, which were published in 2018-2021 by the Publishing House of the University of Zielona Gora.
Keywords: jazz; big band; composition; arrangement; music for big band; conductor